Mondor’s disease of the breast; Case report. - Çalışkan, Yahya Kemal (Journal of Surgery and Medicine, 2017)
Mondor’s disease is sclerosing thrombophlebitis at anterior chest wall. It was first described by Henri Mondor in 1939. Despite the use of antibiotics, steroids, anticoagulants, no significant benefit was found. Symptomatic measures are sufficient for treatment. Mondor’s disease is a self-limiting disease. Improvement is seen between 3 weeks and 6 months. In these cases, investigations should be done for hidden cancers in other region of the breast. In this study, a case with this rare disease was discussed in the context of the literature.